Pan‐Arctic sea ice‐algal chl a biomass and suitable habitat are largely underestimated for multiyear ice. (31st May 2017) - Lange, Benjamin A.; Flores, Hauke; Michel, Christine; Beckers, Justin F.; Bublitz, Anne; Casey, John Alec; Castellani, Giulia; Hatam, Ido; Reppchen, Anke; Rudolph, Svenja A.; Haas, Christian
Abstract: There is mounting evidence that multiyear ice (MYI) is a unique component of the Arctic Ocean and may play a more important ecological role than previously assumed. This study improves our understanding of the potential of MYI as a suitable habitat for sea ice algae on a pan‐Arctic scale. We sampled sea ice cores from MYI and first‐year sea ice (FYI) within the Lincoln Sea during four consecutive spring seasons. This included four MYI hummocks with a mean chl a biomass of 2.0 mg/m 2, a value significantly higher than FYI and MYI refrozen ponds. Our results support the hypothesis that MYI hummocks can host substantial ice‐algal biomass and represent a reliable ice‐algal habitat due to the (quasi‐) permanent low‐snow surface of these features. We identified an ice‐algal habitat threshold value for calculated light transmittance of 0.014%. Ice classes and coverage of suitable ice‐algal habitat were determined from snow and ice surveys. These ice classes and associated coverage of suitable habitat were applied to pan‐Arctic CryoSat‐2 snow and ice thickness data products. This habitat classification accounted for the variability of the snow and ice properties and showed an areal coverage of suitable ice‐algal habitat within the MYI‐covered region of 0.54 million km 2 (8.5% of total ice area). This is 27 times greater than the areal coverage of 0.02 million km 2 (0.3% of total ice area) determined using the conventional block‐model classification, which assigns single‐parameter values to each grid cell and does not account for subgrid cell variability. This emphasizes the importance of accounting for variable snow and ice conditions in all sea ice studies. Furthermore, our results indicate the loss of MYI will also mean the loss of reliable ice‐algal habitat during spring when food is sparse and many organisms depend on ice‐algae. Abstract : We sampled sea ice from the so‐called Last Ice Area, an under‐represented region home to the last remaining really thick, old Arctic sea ice. We measured ice algae biomass values among the highest ever reported for old Arctic sea ice. This was attributed to the typically low‐snow cover of hummocks resulting from wind‐induced snow redistribution, which allowed for continuously suitable light conditions for algal growth despite ice thicknesses over 4 m. Hummocks were identified as common suitable MYI habitat features with an average coverage of 33%. Accounting for the spatial variability of hummocks within a pan‐Arctic habitat classification resulted in nearly 30 times more suitable habitat. This is likely a conservative estimate because we did not consider the potential of horizontal light scattering around hummocks, which would further increase the coverage of suitable habitat. Our findings indicate that losing "the Last Ice Area" will have profound ecological consequences far exceeding our current projections.